Firmware development : a guide to specialized systemic knowledge - Banik, Subrata; Zimmer, Vincent (Apress, 2022)
Build your own system firmware. This book helps you understand system firmware architecture and minimalistic design, and provides a specialized knowledge of firmware development. The book includes guidance on understanding the system firmware build procedure, integrating pieces of firmware and allowing configuration, updating system firmware, creating a development infrastructure for allowing multi-party collaboration in firmware development, and gaining advanced system firmware debugging knowledge. After reading the book you will be able to assume better control while developing your own firmware and know how to interact with native hardware while debugging. You will understand key principles for future firmware development using newer technology, and be ready for the introduction of modern safe programming languages for firmware development.